Learning to Be Different: Quantitative Research in Economics and Political Science - Libman, Alexander; Justus Liebig University Giessen (My University, 2012)
The comment addresses the subtle differences that exist between economics and political science in terms of how the standards for the empirical quantitative research are set. It shows that the common methodology is applied by the disciplines in a different fashion. These differences could become obstacles for communication, but could also provide fruitful background for discussion of disciplines, if one explicitly takes them into account.
Keywords: ddc:100; ddc:330